Tindak Tutur Direktif Ustaz Hanan Attaki dalam Video #LibatinAllah dan #SharingNight pada Kanal YouTube Hanan Attaki - Gisa Dewantara; Anggita Fitrotunnisa Purbaningrum; Amalia Safira; Fivian Ircham Faiq; Afifah Isda Ilaiha; Asep Purwo Yudi Utomo; Yusro Edi Nugroho; Desi Novita Sari; Najwa Faradilah Tri (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This research discusses the main problem in the form of directive speech acts. Directive speech acts as an incentive for the listener to perform the action intended by the speaker. Language is a means of communication between members of society in the form of sound symbols produced by the human speech organs. Communication is not only about speaking and writing; it also includes body language, facial expressions, and even modern media such as text messages and social media. Therefore, this research will discuss one study of pragmatics, namely speech acts. Many actions can implement direct speech acts, one of which is in the activity of preaching. This research aims to determine the function of speech used by the Ustaz in preaching. The research method used is qualitative with descriptive methods and uses the technique of listening and taking notes in data collection and uses contextual data analysis techniques. The results of the study indicate that the Ustaz uses several directive speech acts with his listeners. The functions of the utterances spoken were ordering 8, commanding 6, inviting 9, suggesting 12, asking 20, requesting 9, and prohibiting 7. The dominant form of speech was asking 20 questions. Through this research, the public is expected to understand how language strategies (especially directive speech acts) are used by speakers or preachers to convey messages that are more persuasive and more easily accepted, especially within the local community.